ANTI-TRYPANOSOMA ACTIVITY OF ETHANOLIC EXTRACT OF NEEM LEAF (Azadirachta indica) ON Trypanosoma evansi IN RATS (Rattus norvegicus) - Fahrimal, Yudha; Maghfirah, Siti; Rinidar, Rinidar; Azhar, Al; Asmilia, Nuzul; Erina, Erina (Universitas Syiah Kuala, 2017)
The aim of this study was to determine the effect of neem leaf extract (Azadirachta indica) on parasitemia of rats infected with Trypanosoma evansi (T. evansi) Aceh local isolate. A total of 24 male rats aged three months were used in this study and randomly divided into six treatment groups equally. The negative control group (K0) without T. evansi infection and neem leaf extract, the positive control group (K1) was infected with T. evansi but no neem leaf extract given, group K2, K3, K4, and K5 were infected with 5x104 T. evansi and were given neem leaf extract after patent infection with dose of 50, 100, 400, and 800 mg/kg BW respectively. The extract was given orally for three consecutive days. On the fourth day, rat blood was drawn for parasitemia examination. The results showed that no T. evansi detected in rats in negative control group (K0), while parasitemia in group K1; K2; K3; K4; and K5 was 12,295 x106/mL; 10,495 x106/mL; 9,360 x106/mL; 5,080x106/mL; and 2,398x106/mL of blood, respectively. Percentage of inhibition of parasitemia in K2, K3, K4, and K5 reached 14.64, 23.78, 58.68, and 80.50%, respectively. Based on the result of the study, neem leaf extract of 800 mg/kg BW gave the highest reduction of parasitemia in rats infected with T. evansi.